2015
DOI: 10.3892/ijmm.2015.2358
|View full text |Cite
|
Sign up to set email alerts
|

GNRs@SiO2-FA in combination with radiotherapy induces the apoptosis of HepG2 cells by modulating the expression of apoptosis-related proteins

Abstract: The aim of the present study was to examine the apoptosis of the hepatocellular carcinoma cell line, HepG2, induced by treatment with folic acid-conjugated silica-coated gold nanorods (GNRs@SiO2-FA) in combination with radiotherapy, and to determine the involvement of apoptosis-related proteins. An MTT colorimetric assay was used to assess the biocompatibility of GNRs@SiO2-FA. The distribution of GNRs@SiO2-FA into the cells was observed using transmission electron microscopy (TEM). HepG2 cells cultured in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The surface functionalization of Fe 2 O 3 @Au NPs with FA thus provides an active targeting strategy that directs the NPs towards the cell surface FA receptor, leading to enhanced uptake and efficient internalization of the NPs via receptor-mediated endocytosis [24,25]. For example, Gao et al [44] evaluated the targeting efficiency of FA-conjugated silica-coated gold nanorods (FA-SiO 2@ AuNR) towards the HepG2 hepatocellular carcinoma cells and reported a 2.65-fold higher cellular uptake rate for this noncomplex in comparison to the non-FA conjugated nanocomplex. In another study, the facility of FA targeting was utilized for improving the PTT efficiency of the KB cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The surface functionalization of Fe 2 O 3 @Au NPs with FA thus provides an active targeting strategy that directs the NPs towards the cell surface FA receptor, leading to enhanced uptake and efficient internalization of the NPs via receptor-mediated endocytosis [24,25]. For example, Gao et al [44] evaluated the targeting efficiency of FA-conjugated silica-coated gold nanorods (FA-SiO 2@ AuNR) towards the HepG2 hepatocellular carcinoma cells and reported a 2.65-fold higher cellular uptake rate for this noncomplex in comparison to the non-FA conjugated nanocomplex. In another study, the facility of FA targeting was utilized for improving the PTT efficiency of the KB cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al reported a targeted chemotherapy strategy for the efficient delivery of gold nanoclusters (AuNCs) carrying cisplatin prodrug and demonstrated an accelerated cellular internalization and enhanced tumour accumulation accompanied by the retention of the nanocarriers due to FA modification [36]. Remarkable successes in improving radiotherapy effectiveness have also been provided by utilizing FA-modified AuNPs [37]. Furthermore, in our previous works, we have demonstrated the positive impact of FA targeting on the increase in the photothermal therapy efficiency of AuNPs [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2017;Jiang et al, 2017). Consequently, GSH-responsive become one of most popular redox-responsive precision delivery strategies because of the higher GSH level in intracellular matrix of HCC cells than that in extracellular matrix or intracellular matrix of normal Chen et al, 2010Chen et al, , 2019Gao B. et al, 2015;Lv et al, 2015;Wang Y. et al, 2016;Wang et al, 2017a,b; RGD Integrin SMMC-7721, HepG2, Huh7…”
Section: Internal Stimulimentioning
confidence: 99%
“…Usually normal cells possess a higher heat tolerance over cancer cells at elevated temperatures around 43 • C, so the heat generated (43 • C) would trigger the death of tumor cells only (El-Boubbou, 2018). Gao B. et al (2015), reported MSNs with gold core acted as a radiation sensitizer, thereby inducing the more effective radiotherapy by iodine 125 seed. Furthermore, Wang et al (2019) rethink that radiosensitization strategy is not sufficient because of the hypoxic microenvironment in HCC, so they fabricated Janus-structured gold triangle-mesoporous silica nanoparticles to ameliorates hypoxia through PTT generated by gold triangle.…”
Section: Phototherapy/sonodynamic Therapy (Sdt)mentioning
confidence: 99%